Unfolding COVID-19 vaccine communication campaigns in China’s neighborhoods: a qualitative study of stakeholders’ narratives - Yang, Ronghui; Han, Yanchao (Frontiers in Public Health, 2023)
Introduction The Chinese state has recently implemented the COVID-19 Vaccine Communication Campaign (CVCC) to counter vaccine hesitancy. Nonetheless, the extant literature that examines COVID-19 vaccine acceptance has less represented COVID-19 vaccine communication efforts. Methods To address this lacuna, we qualitatively explored how CVCCs were organized in Chinese communities by investigating 54 Chinese stakeholders. Results This study indicates that the CVCC was sustained by top-down political pressure. CVCCs’ components involve ideological education among politically affiliated health workers, expanding health worker networks, training health workers, implementing media promotion, communicating with residents using persuasive and explanatory techniques, encouraging multistakeholder partnerships, and using public opinion-steered and coercive approaches. While CVCCs significantly enhanced COVID-19 vaccine acceptance, lacking open communication, stigmatizing vaccine refusers, insufficient stakeholder collaboration, and low trust in the COVID-19 vaccination program (CVP) eroded the validity of CVCCs. Discussion To promote the continuity of CVCCs in China, CVCC performers are expected to conduct open and inclusive communication with residents. Furthermore, CVP planers should create robust partnerships among health workers by ensuring their agreements on strategies for implementing CVCCs and optimize COVID-19 immunization service provision to depoliticize CVPs. Our study will not only deepen global audiences’ understanding of CVCCs in authoritarian China but also offer potential neighborhood-level solutions for implementing local and global public health communication efforts.